THE IMPORTANCE OF CLASSROOM GAMES IN TEACHING ENGLISH - Xusanova Mukaddas Mavlonovna (PEDAGOGS, 2024)
Abstract: This article discusses the importance of teaching English and the role of games in teaching young learners. It discusses the problems of teaching English to young learners in educational organizations. Some different kinds of classroom games; “group games”, “word bingo”, “charades” “spelling bee”, “ Pictionary” and “Simon says” were conducted in this study. the. It also includes effective and fun games for English teachers to use in the classroom.